Penerapan Projek Penguatan Profil Pelajar Pancasila Dan Profil Pelajar Rahmatan Lil Alamin (P5P2RA) Di Madrasah Ibtidaiyah - Latifah Alimuninggar Latifah; Triwid Syafarotun Najah; Rahmad Rahmad (Lembaga Dongan Dosen, 2025)
The aim of this research is to describe the implementation of the Project for Strengthening the Pancasila Student Profile and Rahmatan Lil Alamin Student Profile (P5P2RA) at Madrasah Ibtidaiyah. The research method used is descriptive qualitative. The subjects in this research were class V students. The research informants were the homeroom teacher. Data collection techniques in this research used observation, interviews and documentation. The data analysis technique uses the Miles and Huberman technique, which consists of extracting data, reviewing data, until obtaining saturated data, collecting data, reducing data, presenting data, and the final step of making conclusions. The results of this research show that the implementation of the project to strengthen the profile of Pancasila students and the profile of Rahmatan Lulu Alamin students (P5P2RA) has been implemented at MI Islamiyah Palangka Raya. This application is able to provide knowledge in order to strengthen students' character and gain insight from their environment and students become encouraged to contribute to the environment.